REASSESSING THE ROLE OF HOMOCYSTEINE AND HOLOTRANSCOBALAMIN LEVELS IN DIAGNOSING VITAMIN B12 DEFICIENCY ANEMIA - TRIPATHI, SHWETA; CHOUREY, NIRAJ; RN, HIREMATH; MODI; DK, SINHA (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Background: Vitamin B12 deficiency can lead to irreversible neurological damage, megaloblastic anemia, osteoporosis, cerebrovascular, and cardiovascular diseases, and thus, early diagnosis is essential. Objective: The objective of the study was to assess homocysteine (Hcy) and holotranscobalamine (HoloTC) levels among patients with Vitamin B12 deficiency and to see if Hcy and HoloTC level assay can help us in diagnosis of Vitamin B12 deficiency. Methods: We carried out a cross-sectional observational study on 60 patients of Sr. B12 deficient male and female patients between the ages of 18 and 65 years in IPD and OPD patients at multispecialty hospital. Data were collected from predefined pro forma and were asked about their diet, socioeconomic status, and history. Then, these patients further undergone anthropometric measurements and investigated for Hcy and HoloTC level. The statistical analysis was done using Statistical Package for the Social Sciences (SSPS) software (version 11). Results: About 60% of cases were vegetarian and 40% of cases were non-vegetarian. Mean age of study participants was 43.67 years, mean of mean cellular volume was 90.7 fl, mean of B12 was 138 pmol/L, mean of HoloTC was 60.84 pmol/L, and mean of Hcy was 34.17 umol/L. Out of 60 patients, 10 patients had anemia, 21 patients had neurological manifestation, and 29 patients had gastrointestinal (GI) manifestation. In male group, out of 32, 11 patients had HoloTC <8.9, 19 patients had value between 8.9 and 128, and two patients had HoloTC more than 128. In female group, out of 28, seven patients had HoloTC <8.9, 14 patients had value between 8.9 and 128, and seven patients had HoloTC >128. In group of 32 male patients, none of male patients showed Hcy value <5.9, four patients showed Hcy between 5.9 and 16, and 28 patients showed Hcy value >16. Out of 28 female patients, none of female patients showed Hcy <3.36, nine patients showed Hcy between 3.36 and 20.4, and 19 patients showed Hcy >20.4. p <0.001 is highly statistically significant. Conclusion: In our study, we found that 31.33% of cases also showed decreased HoloTC along with B12 deficiency, but this correlation was statistically insignificant. We also found that 78.33% of cases showed increased Hcy along with serum B12 deficiency, which was statistically significant, so we concluded that there is a strong association between serum B12 and Hcy. We found that all patients with elevated Hcy also had low HoloTC except in two cases, but this correlation was not found to be statistically significant.